Clinical Oral Findings and Salivary Analysis of Patients with and without Diabetes Mellitus - Zohaib Ahmad, Shahida Maqbool, Sobia Siddique, Kanza Nawadat, Maham Niazi, Sania Saqib (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The salivary composition in diabetic patients varies depending on the type of saliva examined (whole or parotid, resting or stimulated) and the choice of participants insulin-dependent diabetes mellitus (IDDM) or non-insulin-dependent diabetes mellitus (NIDDM) patients, or a heterogeneous population with various additional systemic diseases or treatments. In Pakistan there is very few studies done on the clinical significance of saliva amongst diabetic patients. Objective: Clinical oral findings and salivary analysis of patients with and without diabetes mellitus Study Design: Case-control study Study Setting: This study was conducted at Department of Oral Biology Akhtar Saeed Medical and Dental College, Lahore from September 2022 to February 2023. Methodology: Out of 421 participants 228 were healthy taken as control and 193 were diabetic patients taken as cases were enrolled in this study. The questionnaire was made to describe the demographic variables age, gender, weight and height for BMI, educational status, socioeconomic status, marital status, and ethnicity. The biochemical parameters were estimated in saliva, collected from diabetic and non-diabetic participants. The 5ml saliva was collected from case and control participants in container and aliquoted at -800C. The samples were thawed at the time of estimation. The salivary biochemical parameters including glucose (mg/dl), insulin (IU/ml), creatinine (umol/L), urea (mml/L), albumin (md/dl), Lactoferrin (ug/ml) and IgA (mg/dl) were done in the lab and estimated through Randox kit according to the manufacturer protocol. The statistical analysis was done by using SPSS version 20. Results: The research included 421 participants in which 294 men (69.8% of the total) and 127 women (30.2% of the total). The average age was 26.4±5.1 years (range: 16.0 to 48.0) of both groups enrolled participants. While the mean of BMI was 23.4±4.5 Kg/m2 (range: 15.10 to 41.90). In this study very low- income status (73.9%) and high frequency of married with 84.6% were enrolled. Diabetics also had considerably higher levels of creatinine, urea, lactoferrin and IgA in the saliva of diabetic patients (p=0.0001). However, albumin was significantly low in diabetic saliva as compared to healthy participants (p=0.015). Practical implication: Studies towards the effects of diabetes mellitus (DM) on oral health has been conducted, but it is not yet known how common oral manifestations of the disease are or how widespread these effects are, especially in Pakistan. The purpose of this research was to compare the effects of diabetes on the dental health and salivary evaluation of people with and without the disease. Conclusion: New information on salivary parameters and oral results on Pakistani population with and without diabetes was presented in this research. The major results showed that those with diabetes had a decreased salivary flow rate, an increase in salivary glucose, and an increase in urea, creatinine, lactoferrin and IgA concentrations. However, the albumin is low in concentration. The results showed that the clinical significance of saliva amongst diabetic patients and can be used as diagnostic marker. Keyword: Saliva, biochemical parameters, diabetes mellitus, glucose, urea, Albumin